Urgensi Implementasi Asas Legalitas Dalam Penyelenggaraan Pemerintahan Desa - Fallahiyan, Muh.Alfian; Khair, H.A; Kafrawi, Kafrawi; Purnomo, Chrisdianto Eko; Saleh, M. (LPPI UMN AL WASHLIYAH, 2025)
The principle of legality is the most fundamental principle in the administration of government, including in the administration of village governance. All mechanisms of governance and policymaking must be based on and aligned with the relevant laws and regulations. In the current implementation of village governance, numerous legal violations still occur, such as abuse of authority, corruption, and other misconducts, all of which stem from the failure to uphold the principle of legality. Therefore, it is deemed necessary to conduct legal education aimed at enhancing the understanding of village government officials regarding the importance of comprehending and applying the principle of legality in village governance. This is essential to ensure that the implementation of governance and any policies made do not lead to legal problems. The methods used in this legal outreach include lectures, discussions, and legal consultations. This study concludes that village government officials have not yet fully understood the principle of legality. Through this legal education, it is expected that they will gain a clearer understanding of the concept and be able to implement it effectively in the administration of village governance.